Interpreting the flexibilities under the TRIPS agreement - Carlos María Correa (South Centre, 2021)
While the TRIPS Agreement provides for minimum standards of protection of intellectual property, it leaves a certain degree of policy space for WTO members, whether developed or developing countries, to implement the Agreement's provisions in different manners, to legislate in areas not subject to the minimum standards under the Agreement, and to develop legal interpretations of such provisions to determine the scope and content of the applicable obligations. This paper focuses on some aspects of how panels and the Appellate Body of the WTO have interpreted said provisions. The paper also draws general conclusions for the implementation of TRIPS flexibilities, which are of crucial importance for the design of a pro-competitive intellectual property system and, in particular, for achieving public health objectives, as specifically recognized by the Doha Declaration on TRIPS and Public Health.
Keywords: 300; Appellate Body; Biologics; Bolar; Competition Law; Compulsory Licenses; Disclosure; Doha Declaration on the TRIPS Agreement and Public Health; Flexibilities; GATT; Government Use; Intellectual Property; Intellectual Property Rights (IPRs); IP Enforcement; Least Developed Countries (LDCs); Parallel Importation; Patent; Patentability Criteria; Public Health; Research Exception; Security Exception; Test Data Protection; TRIPS; World Trade Organization (WTO)